2021
DOI: 10.1128/mbio.03380-20
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of CsrA in Vibrio cholerae

Abstract: CsrA is a posttranscriptional global regulator in Vibrio cholerae. Although CsrA is critical for V. cholerae survival within the mammalian host, the regulatory targets of CsrA remain mostly unknown. To identify pathways controlled by CsrA, RNA-seq transcriptome analysis was carried out by comparing the wild type and the csrA mutant grown to early exponential, mid-exponential, and stationary phases of growth. This enabled us to identify the global effects of CsrA-mediated regulation throughout the V. cholerae g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…This signaling circuitry is highly conserved in γ-proteobacteria ( 42 , 43 , 44 ), preserving most of its general characteristics. However, the genes whose expression are modulated by the BarA/UvrY/CsrA regulatory cascade and hence the physiological response, may vary significantly among bacteria ( 10 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ). Here, we found that the input domain of the BarA/UvrY system of E. coli differs from that of the homologous GacS/GacA of P. aeruginosa, in that the former has evolved to recognize an uncharged signal.…”
Section: Resultsmentioning
confidence: 99%
“…This signaling circuitry is highly conserved in γ-proteobacteria ( 42 , 43 , 44 ), preserving most of its general characteristics. However, the genes whose expression are modulated by the BarA/UvrY/CsrA regulatory cascade and hence the physiological response, may vary significantly among bacteria ( 10 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ). Here, we found that the input domain of the BarA/UvrY system of E. coli differs from that of the homologous GacS/GacA of P. aeruginosa, in that the former has evolved to recognize an uncharged signal.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the repressive function of Hfq can be antagonized through sequestration by the regulatory RNA CrcZ, containing multiple A-rich motifs, which in turn results in de-repression of Hfq and Hfq/Crc target genes (Figures 2 and 3b). The CsrA/RsmA family of RNA-binding proteins governs virulence gene expression in pathogenic bacteria [173][174][175][176][177][178], including Pae [139,179]. Members of this family usually negatively regulate translation of target mRNAs through binding to stem-loop structures present in their 5 UTR that contain exposed GGA motifs [27,139,173,[180][181][182][183][184].…”
Section: Translational Repressors and Their Rna Decoysmentioning
confidence: 99%
“…The CsrA/RsmA family of RNA-binding proteins governs virulence gene expres in pathogenic bacteria [173][174][175][176][177][178], including Pae [139,179]. Members of this family usu negatively regulate translation of target mRNAs through binding to stem-loop struct present in their 5′UTR that contain exposed GGA motifs [27,139,173,[180][181][182][183][184].…”
Section: Translational Repressors and Their Rna Decoysmentioning
confidence: 99%
“…The VarS/VarA system also contributes to the dissemination of V. cholerae from the host into the environment (10). Moreover, in conjunction with CsrA, this TCS is known to be involved in the regulation of central carbon metabolism, iron uptake, lipid metabolism, flagellum-dependent motility, and other phenotypes (11,12). Collectively, signaling through the VarS/VarA-CsrA circuit therefore affects the environmental lifestyle of V. cholerae as well as its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%